If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2x+3)(x=5)
We move all terms to the left:
(2x+3)(x-(5))=0
We multiply parentheses ..
(+2x^2-10x+3x-15)=0
We get rid of parentheses
2x^2-10x+3x-15=0
We add all the numbers together, and all the variables
2x^2-7x-15=0
a = 2; b = -7; c = -15;
Δ = b2-4ac
Δ = -72-4·2·(-15)
Δ = 169
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{169}=13$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-7)-13}{2*2}=\frac{-6}{4} =-1+1/2 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-7)+13}{2*2}=\frac{20}{4} =5 $
| 5•21^5x=16 | | (x+8)^2+x^2=900 | | -49-3x=4x | | 10y-6y+17=3 | | (3m+13)°=31° | | -5=6x-8 | | t/−4=9. | | 7x-4x-10=3x+10 | | (a+4)÷11=-3 | | 975(15)^x=615(25)^x | | 7(3b+5)=-17-9b | | 6f+15=11f−25 | | u÷4=9.5 | | B÷-6+12=5b | | .6f+15=11f−25 | | H=60-4m | | 4y=y^2+2y | | m=1/3;(3,2) | | (15+13)n-6=7n-24 | | C=0.09s | | 3x-6=2x^2+7x-4 | | 2p-2.1p+55.68=12p+5537837.824763 | | 4x+15=10x-5 | | 2/p+3=7/28p | | 10-3=8x-5-14x | | (4/5)x+3=2x-1 | | 4p-72=-32 | | x+2x-6=159 | | -2-x+4(4-2x-3)=-8x+1 | | 159=x+2x-6 | | 5^(-2x)=4 | | 4x^2-30x+48=0 |